Optimizing H2/CO2 binary gas mixture separation using Li-K-ETS-10 zeolite: Breakthrough analysis and impact of operational conditions - Shrotri, Aadesh R.; Nandanwar, Sachin U. (International Journal of Hydrogen Energy, 2025)
The polycation-exchanged ETS-10 (Li-K-ETS-10) zeolite was employed as a sorbent in breakthrough experiments using a binary H2/CO2 (75/25%) gas mixture. The data compared with parent adsorbent (NaK)-ETS-10, and mono cation exchange of ETS-10 (K-ETS-10 and Li-ETS-10). Adsorbents underwent for various characterization including XRD, Raman, FTIR, EDS, CO2-TPD, BET surface area, and pore diameter of samples to understand the physicochemical properties. CO2-TPD shows that Li-K-ETS-10 has higher basicity than parent (NaK)-ETS-10. The process parameters were optimized to ensure a higher CO2 sorption capacity and better H2 purity including effects of flow rate, pressure, temperature, feed concentration, bed height, and recyclability. The adsorption capacities of CO2 and H2 were found to be 1.57 mmol g- 1 and 0.24 mmol g-1, respectively, at 1 bar and a flow rate of 200 mL min- 1. These values represent a 40% improvement over (NaK)-ETS-10 and a-10.4% improvement over Li-ETS-10. At 6 bar, the CO2 and H2 adsorption capacities reached 2.79 mmol g- 1 and 0.22 mmol g-1, respectively. The higher CO2 sorption over Li-K-ETS-10 leads due to improve in basic sites and physical properties of sample compare to studied adsorbent. The experimental data of binary gas mixture was used to evaluate the kinetic models including Thomas, and Yoon-Nelson. This results implies that Li-K-ETS-10 is the promising candidates for H2 separation from binary gas mixture.
Keywords: adsorbent; Binary gas stream; Breakthrough study; H2/CO2 separation; Kinetic modelling; Li-K-ETS-10